Teachers' Perspectives of the New Western Australian Earth and Environmental Science Course: Lessons for the Australian Curriculum - Dawson, Vaille; Moore, L. (Australian Science Teachers Association, 2011)
In 2007, a new upper secondary course, Earth and Environmental Science (EES) was introduced in Western Australia. The development and implementation of the course was supported by Earth Science Western Australia (ESWA), a consortium of universities, the CSIRO and other organisations. The role of ESWA is to support the teaching of earth science in schools by developing teaching and learning resources, provide professional development for teachers and assist with field experiences for students. Since 2008, EES has been taught in twenty-five schools with 417 students enrolled increasing to 667 students in 2010. In 2009 an evaluation of the implementation of EES was conducted. A total of twenty-seven EES teachers from twenty-four schools were interviewed about their background and professional development in EES, resources used and their perceptions of the course. Results indicate that: few teachers have educational qualifications in both earth science and environmental science; teachers need to be provided with quality resources and relevant professional development that depends on their background; teachers and their students find the earth science topics difficult. The findings of this study have implications for the development and implementation of the proposed Earth and Environmental Science course in the National Science Curriculum.